BIOCIDAL ACTIVITY OF BACILLUS THURINGIENSIS H-14 TOXIN ON THREE SPECIES OF MOSQUITOES - GOKHALE, M. D.; MOURYA, D. T.; BARDE, P. V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Comparative toxicity of Bacillus thuringiensis israelensis H-14, commercial product in aqueous and granular formulations, were studied on the three species of mosquitoes, Anopheles stephansi, Culex quinquefasciatus and Aedes aegypti. It was observed that both the formulations were equally effective against these three species. Further biological studies on the pesticide resistant and susceptible strains of Ae. aegypti showed that the toxin was highly effective on the larvae irespective of their pesticide susceptibility status. In the light of these observations the use of bio-pesticides for the control of these vector mosquitoes is discussed.